2021
DOI: 10.3390/ijms22179114
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated Radiotherapy Upregulates Several Immune Checkpoint Molecules in Head and Neck Squamous Cell Carcinoma Cells Independently of the HPV Status While ICOS-L Is Upregulated Only on HPV-Positive Cells

Abstract: While the treatment of squamous cell carcinoma of the head and neck (HNSCC) with radiotherapy (RT) is complemented more and more by immunotherapy in clinical trials, little is known about the impact of the human papillomavirus (HPV) status or the applied RT scheme on the immune phenotype of the tumor cells. Therefore, we aimed to examine the impact of the HPV status of four human HNSCC cell lines on cell death and the expression of immune checkpoint molecules (ICMs) after RT with either hypofractionation irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 63 publications
3
4
1
Order By: Relevance
“…In contrast, irradiating HPV-positive cell lines resulted in a higher necrotic cell death rate, which was also recently shown by Wimmer et al. [13] . Thus indicating, that the HPV-negative cell lines killed by RT alone or in combination with docetaxel could rather suppress immune response, whereas the treated HPV-positive cell lines would stimulate an immune response, supporting better outcome of HPV-positive associated head and neck tumors.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, irradiating HPV-positive cell lines resulted in a higher necrotic cell death rate, which was also recently shown by Wimmer et al. [13] . Thus indicating, that the HPV-negative cell lines killed by RT alone or in combination with docetaxel could rather suppress immune response, whereas the treated HPV-positive cell lines would stimulate an immune response, supporting better outcome of HPV-positive associated head and neck tumors.…”
Section: Discussionsupporting
confidence: 78%
“…It has been generally suggested that HPV positive HNSCC are more immunogenic compared to HPV negative ones [12] . We have just recently identified that following RT, the expression of the inducible co-stimulatory molecule ligand (ICOS-L) is upregulated only on HPV positive HNSCC cell lines [13] . As ICOS/ICOSL signaling leads to the activation, proliferation and survival of cytotoxic T cells [14] , it might foster RT-induced anti-HNSCC tumor responses.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous in vitro and in vivo examinations using various cancer cell lines and models, we revealed that it is not just PD-L1 which is upregulated by RT, but rather both immune inhibitory and immune stimulatory ( 50 53 ) ICM expression is significantly increased on the surface of TNBC cells following (hypofractionated) irradiation. This has already been demonstrated in other settings and tumor entities ( 54 , 55 ).…”
Section: Discussionsupporting
confidence: 67%
“…However, besides OX40-L, the other immune-activating ICMs (ICOS-L, CD27-L, CD137-L) examined were not strongly affected by RT and HT (not shown). This is in contrast to other tumor entities, such as, e.g., head and neck cancer, where ICOS-L is upregulated on HPV-positive cancer cells after RT [68].…”
Section: The Combination Of Hyperthermia and Radiotherapy Affects Par...contrasting
confidence: 63%